Seismological experiment at Strokkur from 2020 ... - Eibl, Eva P.S.; Hersir, Gylfi P.; Vollmer, Daniel (GFZ Data Services, 2025)
Seismological experiment at Strokkur from 2020" is a seismological experiment realized at the most active geyser on Iceland by Eva Eibl (University of Potsdam) in collaboration with Gylfi P. Hersir formerly at ISOR Iceland. The geyser is part of the Haukadalur geothermal area in south Iceland, which contains numerous geothermal anomalies, hot springs, and basins (Walter et al., 2018). Strokkur is a pool geyser and has a silica sinter edifice with a water basin on top, which is about 12m in diameter with a central tube of more than 20m depth. The aim of the seismic experiment is to monitor eruptions of Strokkur geyser from March 2020 using three broadband seismic stations (Nanometrics Trillium Compact 120s). Sensors were buried at distances of 38.8m (GE4, SE), 47.3m (GE3, SW), and 42.5m (GE2, N) from Strokkur center. Within this time period about 1 month of data is missing due to power outages. At any other times at least one station recorded the eruptions. From this dataset, converted to MSEED using Pyrocko, ...